New and validated hyphomycetes taxa described by A. Rambelli from Costa Rica - Castañeda-Ruiz, Rafael F.; Mardones, Melissa; Souza, Maria G.a.p.; Li, De-Wei; Kirk, Paul M.; Gusmão, Luís F.p. (Phytotaxa, 2024)
N/A